Load and failure behavior of human muscle samples in the context of proximal femur replacement. Issue 1 (December 2016) - Schleifenbaum, Stefan; Schmidt, Michael; Möbius, Robert; Wolfskämpf, Thomas; Schröder, Christian; Grunert, Ronny; Hammer, Niels; Prietzel, Torsten
Abstract Background To ensure adequate function after orthopedic tumor reconstruction, it is important to reattach the remaining soft tissue to the implant. This study aimed at obtaining mechanical properties of textile muscle-implant and muscle-bone connections in a preliminary test. Methods Two groups of soft-tissue attachment were mechanically tested and compared: Native bone-muscle samples obtained from human femora and muscles attached to a prosthetic implant by means of Trevira® attachment tubes. Additionally, muscle samples were tested with muscle fibers aligned parallel and perpendicular to the tension load. A uniaxial load was exerted upon all samples. Results Failure loads of 26.7 ± 8.8 N were observed for the native bone-muscle group and of 18.1 ± 9.9 N for the Trevira® group. Elongations of 94.8 ± 36.2 % were observed for the native bone-muscle group and 79.3 ± 51.8 % for the Trevira® group. The location of failure was mainly observed in the central area of the muscle fibers. Muscle fibers with parallel fiber orientation (47.6 ± 11.5 N) yielded higher tensile strength than those with perpendicular fiber orientation (14.8 ± 4.1 N). Conclusions Our experiments showed that higher forces were transmitted in the origin and insertion areas than in areas of flat soft tissue reconstruction using attachment tubes. The data indicate that the tested material allows reattaching muscles, but without reinforcing the insertion site. Therefore, attachment tubes with region-dependent and potentially anisotropic material behavior might be advantageous to optimize muscle-bone load transmission after surgery, which may allow lower complication rates and shorter physical recovery.